Selective recovery of vanadium, molybdenum, and nickel from full-particle spent hydrodesulfurization catalysts via microwave roasting-ammonia leaching - Haoyu Xu; Liang Yu; Zhiyuan Ma; Shuling Fang; Shuai Rao; Dongxing Wang; Lijuan Duan; Hongyang Cao; Zhiqiang Liu (Journal of Environmental Chemical Engineering, 2026)

Methyl jasmonate alleviates chilling-induced browning in peach fruit through transcriptional suppression of PpLAC7 - Lufan Wang; Liang Zhou; Qiaocai Zhang; Huijuan Zhou; Lichao Zhou; Jiaxu Mao; Shiying Zhang; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

AcERF61 transcription factor mediates ethylene-induced kiwifruit softening through directly regulating cell wall degradation genes - Lufan Wang; Jiaxu Mao; Shiying Zhang; Huijuan Zhou; Libin Wang; Liang Zhou; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Purα is an essential host factor for rice stripe virus accumulation and transmission in the small brown planthopper - Shuling Zhao; Chunling Lin; Wenyu Pan; Changyong Liang (Archives of Virology, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

A novel numerical analysis method for the stability of sediment void-type energy storage salt cavern and its application in Tai’an, China - Xiaopeng Liang; Xiuli Ding; Wanrui Hu; Hongling Ma; Shuling Huang; Xilin Shi; Rui Cai; Zhen Zeng; Xuan Wang (Tunnelling and Underground Space Technology, 2026)

Aldometanib mitigates LPS-induced lung fibroblasts injury through the activation of AMPK-mediated signaling pathways - Fangfang Shao; Jianlong Xie; Lili Liang; Shuling Chen; Rilin Zhang (Toxicon, 2025)

Methyl jasmonate regulates the glycolytic pathway and the PpbZIP43-PpFAD2 module to enhance cold resistance in peach fruit - Lufan Wang; Yuxuan Wang; Jiaxu Mao; Huijuan Zhou; Libin Wang; Binger Dai; Liang Zhou; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

High-strength crosslinked MXene/CNT/PEEK composites for electromagnetic interference shielding and infrared camouflage in extreme environments - Yu Bai; Chunqi Guo; Liubo Liang; Shengdao Wang; Xiaohan Mei; Yanxu Lu; Jianpeng Jiao; Guibin Wang; Shuling Zhang (Chemical Engineering Journal, 2025)

Polyetheretherketone-based foam with low reflectivity and high electromagnetic interference shielding effectiveness suitable for harsh service environments - Liubo Liang; Tonghua Wu; Xiaohan Mei; Yu Bai; Chunqi Guo; Yanchao Yang; Guibin Wang; Shuling Zhang; Jianxin Mu (Chemical Engineering Journal, 2025)

Control efficiency and potential mechanisms of chlorogenic acid against postharvest gray mold caused by Botrytis cinerea on peach fruit - Binger Dai; Yuxuan Wang; Huijuan Zhou; Lufan Wang; Liang Zhou; Jiaxu Mao; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2024)

The virulence plasmid associated with AHPND in shrimp appears to have originated from Vibrio owensii through a process of homologous recombination of parental plasmids and the transposable insertion of two large fragments - Yesheng Yan; Haojie Lu; Xiaosha Liang; Tianqi Xu; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Invertebrate Pathology, 2024)

High-throughput relative quantification of fatty acids by 12-plex isobaric labeling and microchip capillary electrophoresis - Mass spectrometry - Zicong Wang; Miyang Li; Shuling Xu; Liang Sun; Lingjun Li (Analytica Chimica Acta, 2024)

Insights into boosting catalytic hydrogen evolution over Co doping Ru nanoparticles - Hao Wen; Ruofan Shen; Yanyan Liu; Xiaoyan Huang; Shuling Liu; Zhikun Peng; Xianli Wu; Xianji Guo; Erjun Liang; Huiyu Yuan; Baojun Li; Jianchun Jiang (Fuel, 2023)

Bacterial diversity of middle ear cholesteatoma by 16S rRNA gene sequencing in China - Qiulin Liang; Ruiqing Long; Shuling Li; Chaowu Jiang; Jingyu Gao; Sheng Cheng; Zhuohui Liu; Biao Ruan (Functional & Integrative Genomics, 2023)
In this study, the bacterial diversity of acquired middle ear cholesteatoma (MEC) was evaluated to reveal its pathogenesis and provides a guide for the use of antibiotics. Twenty-nine cases of acquired MEC and eight cases of healthy middle ears undergoing cochlear implantation (CI) were evaluated. Full-length 16S rRNA gene sequencing was performed to profile the bacterial communities in lesions and healthy tissues of the middle ear. ACE ( P = 0.043) and Chao1 ( P = 0.039) indices showed significant differences in alpha diversity ( P < 0.05). Analysis of PERMANOVA/Anosim using the Bray–Curtis distance matrix results suggested that the between-group differences were greater than the within-group differences ( R = 0.238, P < 0.05, R 2 = 0.066, P < 0.05). Bacterial community analysis revealed that Alphaproteobacteria at the class level and Caulobacterales and Sphingomonadales at the order level were significantly different ( P < 0.05). In the LefSe (Linear discriminant analysis effect size) analysis, Porphyromonas bennonis was elevated, and Bryum argenteum and unclassified Cyanobacteriales were reduced at the species level in MEC ( P < 0.05). Fifteen metabolic pathways were found to be significantly different between the two groups by analysing the abundance of metabolic pathways in level 2 of the Kyoto Encyclopaedia of Genes and Genomes (KEGG). Seven and eight metabolic pathways were significantly elevated in the MEC and control groups, respectively ( P < 0.05). The role of bacteria in the pathogenesis of acquired MEC was further refined through analysis of metabolic pathways. These findings indicate that the acquired MEC and healthy middle ear contain more diverse microbial communities than previously thought.

Synthesis of sodium alginate/phosphorus tetramethylmethyl sulfate biocomposite beads with exceptional adsorption rate for Cr(VI) removal - Shuling Liang; Weiquan Cai; Chengxiong Dang; Xiong Peng; Zhijia Luo; Xingchuan Wei (Journal of Environmental Chemical Engineering, 2023)

Diverse viruses of marine archaea discovered using metagenomics - Yifan Zhou; Liang Zhou; Shuling Yan; Lanming Chen; Mart Krupovic; Yongjie Wang (Environmental Microbiology, 2023)
During the past decade, metagenomics became a method of choice for the discovery of novel viruses. However, host assignment for uncultured viruses remains challenging, especially for archaeal viruses, which are grossly undersampled compared to viruses of bacteria and eukaryotes. Here, we assessed the utility of CRISPR spacer targeting, tRNA gene matching and homology searches for viral signature proteins, such as major capsid proteins, for the assignment of archaeal hosts and validated these approaches on metaviromes from Yangshan Harbor (YSH). We report 35 new genomes of viruses which could be confidently assigned to hosts representing diverse lineages of marine archaea. We show that the archaeal YSH virome is highly diverse, with some viruses enriching the previously described virus groups, such as magroviruses of Marine Group II Archaea (Poseidoniales), and others representing novel groups of marine archaeal viruses. Metagenomic recruitment of Tara Oceans datasets on the YSH viral genomes demonstrated the presence of YSH Poseidoniales and Nitrososphaeria viruses in the global oceans, but also revealed the endemic YSH‐specific viral lineages. Furthermore, our results highlight the relationship between the soil and marine thaumarchaeal viruses. We propose three new families within the class Caudoviricetes for the classification of the five complete viral genomes predicted to replicate in marine Poseidoniales and Nitrososphaeria, two ecologically important and widespread archaeal groups. This study illustrates the utility of viral metagenomics in exploring the archaeal virome and provides new insights into the diversity, distribution and evolution of marine archaeal viruses.

High-purity hydrogen production from phenol on Ni-CaO-Ca12Al14O33 multifunctional catalyst derived from recovered layered double hydroxide - Chengxiong Dang; Shuling Liang; Wenwen Yang; Weiquan Cai (Fuel, 2023)

Heat shock cognate protein 70 is required for rice stripe tenuivirus accumulation and transmission in small brown planthopper - Jie Li; Wenyu Pan; Shuling Zhao; Changyong Liang (Archives of Virology, 2022)

The N-terminal cysteine protease domain of rice stripe tenuivirus Pc1 possesses deubiquitinating enzyme activity - Shuling Zhao; Xiaomei Gu; Jie Li; Changyong Liang (Virus Genes, 2021)

Correction to: Complete genome sequence analysis of the Vibrio owensii strain SH‑14 isolated from shrimp with acute hepatopancreatic necrosis disease - Xiaosha Liang; Liang Zhou; Shuling Yan; Yongjie Wang (Archives of Microbiology, 2020)

Complete genome sequence analysis of the Vibrio owensii strain SH-14 isolated from shrimp with acute hepatopancreatic necrosis disease - Xiaosha Liang; Liang Zhou; Shuling Yan; Yongjie Wang (Archives of Microbiology, 2020)

Intracellular localization of rice stripe virus RNA-dependent RNA polymerase and its interaction with nucleocapsid protein - Shuling Zhao; Jiahui Hao; Yanan Xue; Changyong Liang (Virus Genes, 2015)

The RNA-binding properties and domain of Rice stripe virus nucleocapsid protein - Shuling Zhao; Yanan Xue; Jiahui Hao; Changyong Liang (Virus Genes, 2015)

The Ac124 protein is not essential for the propagation of Autographa californica multiple nucleopolyhedrovirus, but it is a viral pathogenicity factor - Changyong Liang; Dandan Lan; Shuling Zhao; Lulu Liu; Yanan Xue; Yongli Zhang; Yun Wang; Xinwen Chen (Archives of Virology, 2015)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)